Psychometric properties of the Persian version of the Geriatric Anxiety Scale - Shakib, Niloufar; Kachooei, Mohsen (Applied Family Therapy Journal (AFTJ), 2022)
Aim: The aim of this study was to investigate the psychometric properties of the Persian version of the Elderly Anxiety Scale (GAS). Methods: The research was descriptive. The statistical population included all elderly men and women living in Kahrizak nursing home in Tehran. Among them, 250 people (150 females and 100 males) were selected by available sampling method. The instrument used was the Elderly Anxiety Scale (GAS). Confirmatory factor analysis and Cronbach's alpha reliability and retest coefficient were used to evaluate the validity of the scale structure. Data were analyzed using LISREL and SPSS software. Results: The results showed that the Elderly Anxiety Scale (GAS) in the first-order factor structure was confirmed using confirmatory factor analysis. The retest coefficient obtained from the test was estimated at one-week intervals. The Cronbach's alpha of the whole scale is 0.83 and its retest coefficient is 0.81. Conclusion: It can be concluded that the Persian version of the Elderly Anxiety Scale (GAS) has good validity and reliability and is an effective self-report tool for research purposes in the field of aging.